2018
DOI: 10.1097/ccm.0000000000003084
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Analysis of Transcriptomics in Bacterial Sepsis Across Multiple Datasets Reveals Three Robust Clusters

Abstract: The three sepsis subtypes may represent a unifying framework for understanding the molecular heterogeneity of the sepsis syndrome. Further study could potentially enable a precision medicine approach of matching novel immunomodulatory therapies with septic patients most likely to benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
240
0
7

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(261 citation statements)
references
References 51 publications
14
240
0
7
Order By: Relevance
“…These "hyperthermic, slow resolvers" may represent the hyperinflammatory subphenotype. Sweeny et al also identified an "inflammopathic" subtype from sepsis datasets, which included high disease severity, high bandemia, and high mortality [46]. In the present study, we identified a hyperinflammatory subphenotype (group A patients) that was accompanied by elevated baseline values for temperature and white blood cell count.…”
Section: Discussionsupporting
confidence: 51%
“…These "hyperthermic, slow resolvers" may represent the hyperinflammatory subphenotype. Sweeny et al also identified an "inflammopathic" subtype from sepsis datasets, which included high disease severity, high bandemia, and high mortality [46]. In the present study, we identified a hyperinflammatory subphenotype (group A patients) that was accompanied by elevated baseline values for temperature and white blood cell count.…”
Section: Discussionsupporting
confidence: 51%
“…3). Some of this residual heterogeneity is expected, owing to the clinical heterogeneity inherent across sepsis cohorts [40][41][42] , but highlighted the need for a robust training procedure 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the particular genes that best discriminated the high-risk cohort varied by study, this may be due to high correlation among many dysregulated genes, rather than a failure to replicate. Indeed, a metaanalysis by Sweeney et al [123] that included mortality data from 14 diverse datasets of bacterial infection, including both adult and child cohorts, identified three clusters (a high-mortality "inflammopathic" cluster, a low-mortality "adaptive" cluster, and an additional "coagulopathic" cluster characterized by abnormal coagulation profiles) that could be distinguished with an 11-gene signature. They assessed overlap of their signature-based clusters with the high-mortality clusters identified in the MARS and Wong et al pediatric cohorts, and they found substantial overlap in patients identified by each cohort's high-mortality/high-inflammation endotype.…”
Section: Sepsis Gene Expression Studies: Ready For Clinical Launch?mentioning
confidence: 99%